МОВА – НАЙВАЖЛИВІШИЙ НАЦІОНАЛЬНИЙ ІДЕНТИФІКАТОР - Дудко, Ірина (Taras Shevchenko National University of Kyiv (Ukraine), 2021)
[Дель Ґаудіо Сальваторе. Італійсько-українська лексикологія: порівняльний аспект. Del Gaudio Salvatore. Lessicologia dell’ italiano e dell’ ucraino: aspetti comparativi : навч. посіб. Київ, 2020. 156 с.]

[Del Gaudio Salvatore. Italian-Ukrainian lexicology: a comparative aspect. Del Gaudio Salvatore. Lessicologia dell’ italiano e dell’ ucraino: aspetti comparativi. Kyiv, 2020. 156 p.]
LANGUAGE IS THE MOST IMPORTANT NATIONAL IDENTIFIER